Модифицирование углей продуктами пиролиза гетеробиметаллических Mn^II/M^II и Zn^II/M^II (M=Cu, Ni) комплексов для электровосстановления кислорода - Пирский, Ю.К. (Видавничий дім "Академперіодика" НАН України, 2008)
Catalytic activity of oxygen reduction electrocatalysts based on SIT-1 activated carbon, modified by pyrolysis products of heterobimetallic complexes Cu(L)MnCl4, Ni(L)MnCl4, Cu(L)ZnCl4, and Ni(L)ZnCl4 (L =4,6,6-trimethyl-1,9-diamino-3,7-diazanon-3-ene) is studied. The optimal catalyst synthesis conditions, which affect the efficiency of oxygen electroreduction, are determined. Electrocatalysts prepared from heterobimetallic copper complexes are more active than those prepared from nickel complexes.